Economic Active Population in Bulgaria for the Period 2007-2017 - Dynamics of Educational and Age Structure - Atanassova, Margarita (Research Papers, 2020)
The analysis of changes in the economically active population focuses on the period 2007-2017, which covers the first decade of Bulgaria's membership in the European Union. The main purpose of this article is to analyze changes in the age and educational structure of the workforce in the country and to outline challenges in updating employment, education and training policies. The results of the comparative analysis show that in the context of labor force growth in a number of EU countries and in the community as a whole after 2007 in Bulgaria the reverse trend is emerging - the number of economically active population is decreasing. During the period, a number of structural changes occurred in the economically active population in Bulgaria, transforming the contextual framework for formulating and updating employment and human capital policies: polarization of the educational structure of the youth groups of workforce and the relative stability of the share of low-educated young people of working age.
Keywords: Economically active population; Educational structure; Labor force